Peptidoglycan O‐acetylation is functionally related to cell wall biosynthesis and cell division in Streptococcus pneumoniae. Issue 5 (26th October 2017) - Bonnet, Julie; Durmort, Claire; Jacq, Maxime; Mortier‐Barrière, Isabelle; Campo, Nathalie; VanNieuwenhze, Michael S.; Brun, Yves V.; Arthaud, Christopher; Gallet, Benoit; Moriscot, Christine; Morlot, Cécile; Vernet, Thierry; et al.
Summary: The peptidoglycan is a rigid matrix required to resist turgor pressure and to maintain the cellular shape. It is formed by linear glycan chains composed of N ‐acetylmuramic acid‐(β‐1, 4)‐ N ‐acetylglucosamine (Mur N Ac‐Glc N Ac) disaccharides associated through cross‐linked peptide stems. The peptidoglycan is continually remodelled by synthetic and hydrolytic enzymes and by chemical modifications, including O‐acetylation of Mur N Ac residues that occurs in most Gram‐positive and Gram‐negative bacteria. This modification is a powerful strategy developed by pathogens to resist to lysozyme degradation and thus to escape from the host innate immune system but little is known about its physiological function. In this study, we have investigated to what extend peptidoglycan O‐acetylation is involved in cell wall biosynthesis and cell division of Streptococcus pneumoniae . We show that O‐acetylation driven by Adr protects the peptidoglycan of dividing cells from cleavage by the major autolysin LytA and occurs at the septal site. Our results support a function for Adr in the formation of robust and mature Mur N Ac O‐acetylated peptidoglycan and infer its role in the division of the pneumococcus. Abstract : In this study, we have investigated to what extend peptidoglycan O‐acetylation is involved in cell wall biosynthesis and cell division of Streptococcus pneumoniae . We show that O‐acetylation driven by Adr protects the peptidoglycan of dividing cells from cleavage by the major autolysin LytA and occurs at the septal site. Our results support a function for Adr in the formation of robust and mature Mur N Ac O‐acetylated peptidoglycan and infer its role in the division of the pneumococcus.